Emergence of multiple drug resistance Vibrio cholerae O1 in East Delhi - Shukla Das; Shilpee Choudhry; Rumpa Saha; Vishnampettai Ganapathysubramanian Ramachandran; Kamaldeep Kaur; B L Sarkar (Journal of Infection in Developing Countries)
Introduction: Considering the changing geographical and temporal occurrence of Vibrio cholerae, there is a continuing need to monitor the strain characteristics and antibiotic resistance patterns of this pathogen. The present study was conducted to document the changing biology of V. cholerae isolates in and around Delhi, India, and the development of antibiotic resistance.